ZeGo: Development and Validation of a Short Questionnaire to Measure User Satisfaction with e-Government Portals - Javier A. Bargas-Avila; Sébastien Orsini; Marco de Vito; Klaus Opwis (Advances in Human-Computer Interaction)
In recent years, electronic services delivered via the World Wide Web have become increasingly important to governments. Substantial investments have been made to provide crucial services and information to citizens, businesses, and governmental institutions. This paper presents the development of a short questionnaire to measure user satisfaction with e-Governmental portals. After two validations of the instrument with federal e-Governmental portals in Switzerland, a final set of 15 items remained that were tested with 2498 participants. The final version showed high internal consistency (Cronbach's 𝛼) of .91, good item difficulties (.51 to .82), and discriminatory power coefficients (.49 to .81), as well as a moderate average homogeneity of .47. The survey was translated into five languages.